Influenza vaccination among healthcare workers and absenteeism from work due to influenza-like illness in a teaching hospital in Palermo (Italian Journal of Public Health, 2010)
Background: Annual flu vaccination of healthcare workers (HCWs) is recommended worldwide as the bestway to prevent influenza and to avoid its transmission. However, in several European Countries, vaccinationrate among HCWs is still less than 25%. The aim of this study was to determine the HCW vaccination coverageduring a three year period in a large University Hospital, identifying socio-demographic and occupationalvariables involved in the decision to accept influenza vaccination. Moreover, for the 2007-2008 season, wealso assessed the effectiveness of influenza vaccination in reducing influenza-related absenteeism.Methods: During three consecutive influenza seasons (from 2005-2006 to 2007-2008), a cross-sectionalstudy was carried out on all HCWs employed in the “Azienda Ospedaliera Universitaria Policlinico” (AOUP)of Palermo (Italy). Socio-demographic and occupational data of HCWs were collected from administrativehospital personnel records and included gender, age, birthplace, residence, profession and the workplaceunit. In addition, during the 2007-2008 season, a retrospective study was conducted to evaluate absencefrom work due to influenza–like illness (ILI) in vaccinated versus unvaccinated personnel.Results: A total of 7,848 HCW-years were observed and 881 vaccines were administered during the studyperiod. Vaccination rate declined from 14.7% in 2005-2006 to 8.2% in 2007-2008 (Chi-square for trend=53.6,p
Keywords: influenza; vaccination; healthcare workers